(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The traditional switches are positioned in different sections of the home, making it difficult for the user to go close to them to control them, which is especially problematic for the old and crippled. As technology advances, homes are increasingly transitioning from traditional switches to centralized smart control systems with remote-controlled switches. Furthermore, the smart home idea raises the level of living at home. The main goal of this project is to create a real-time home automation system that uses an ESP 32 controller to control appliances with voice commands (Alexa) using a dedicated Android app. The most modern answer is provided by this home automation system, which works with Alexa and smartphones. To do this, a mobile device and an Alexa device are communicated with using an ESP 32 controller with an inbuilt wi-fi module. The switch state is synchronized across the control system, and each user interface displays the current switch status in real time. The system featured a low-cost design, a user-friendly interface, and was simple to install. It was meant to manage electrical gadgets and appliances in the home.